Privacy in the Age of Big Data: Recognizing Threats, Defending Your Rights, and Protecting Your Family - Payton, Theresa; Claypoole, Ted (Rowman & Littlefield Publishers, 2014)
Digital devices have made our busy lives a little easier and they do great things for us, too – we get just-in-time coupons, directions, and connection with loved ones while stuck on an airplane runway. Yet, these devices, though we love them, can invade our privacy in ways we are not even aware of. The digital devices send and collect data about us whenever we use them, but that data is not always safeguarded the way we assume it should be to protect our privacy. Privacy is complex and personal. Many of us do not know the full extent to which data is collected, stored, aggregated, and used. As recent revelations indicate, we are subject to a level of data collection and surveillance never before imaginable. While some of these methods may, in fact, protect us and provide us with information and services we deem to be helpful and desired, others can turn out to be insidious and over-arching. Privacy in the Age of Big Data highlights the many positive outcomes of digital surveillance and data collection while also outlining those forms of data collection to which we do not always consent, and of which we are likely unaware, as well as the dangers inherent in such surveillance and tracking. Payton and Claypoole skillfully introduce readers to the many ways we are “watched” and how to change behaviors and activities to recapture and regain more of our privacy. The authors suggest remedies from tools, to behavior changes, to speaking out to politicians to request their privacy back. Anyone who uses digital devices for any reason will want to read this book for its clear and no-nonsense approach to the world of big data and what it means for all of us.